Preliminary Study: Treatment of Food Industrial Wastewater using Two-Phase Anaerobic Treatments - Ibrahim, Shahrul Shafendy; Abdul Latiff, Ab. Aziz; Daud, Zawawi (International Journal of Integrated Engineering, 2013)
Abstract: Food processing industrial wastewater is well known for its high concentration of COD, BOD and suspended solid. The condition of the wastewater formed makes it illegal for the industry to release the wastewater to the open body of water without essential treatment. The study is conducted on food manufacturing company which specializes in chips export business. The quality of the wastewater produced from the manufacturing is not appropriate to be discharged directly. Thus, a two phase treatment system involving UASB and HUASB reactors as primary treatment and followed by AF reactor as secondary treatment is proposed. Basically, this research will focus on the performance of UASB-AF and HUASB-AF treatment systems and the affect of adding palm oil shell into the HUASB and AF respectively as support media. Parameters measured are pH, COD, NH3-N, oil and grease and total phosphorus. The instruments used for collecting data in this research are pH meter and HACH DR5000. In this research, the highest COD removal for the effluents from the U1 and U2 were at the 14th day with 93.6% removal and at the 62th day with 96.6% each. Meanwhile, in the R2 treatment system, the highest COD removal for the effluents from the H1 and H2 were at the 14th day with 98.3% removal and at 110th day with 97.6% removal. It is hoped that this study will generate useful findings that could be applied to alleviate the current problem at the food factory and also at other food industry in the future.